2018
DOI: 10.1093/mnras/sty919
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Local Group satellite planes

Abstract: We attempt to understand the planes of satellite galaxies orbiting the Milky Way (MW) and M31 in the context of Modified Newtonian Dynamics (MOND), which implies a close MW-M31 flyby occurred ≈ 8 Gyr ago. Using the timing argument, we obtain MW-M31 trajectories consistent with cosmological initial conditions and present observations. We adjust the present M31 proper motion within its uncertainty in order to simulate a range of orbital geometries and closest approach distances. Treating the MW and M31 as point … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 154 publications
(253 reference statements)
2
52
0
Order By: Relevance
“…The outer particles of each disk generally ended up preferentially rotating within a certain plane. If the flyby occurred in a particular orientation, then both simulated 'satellite planes' matched the orientations and spatial extents of the corresponding observed structures (Banik et al 2018). Their best-fitting simulation also matched several other constraints like the timing argument, the statement that the MW and M31 must have been on the Hubble flow at very early times but still end up with their presently observed separation and relative velocity (Kahn & Woltjer 1959).…”
Section: Introductionsupporting
confidence: 57%
“…The outer particles of each disk generally ended up preferentially rotating within a certain plane. If the flyby occurred in a particular orientation, then both simulated 'satellite planes' matched the orientations and spatial extents of the corresponding observed structures (Banik et al 2018). Their best-fitting simulation also matched several other constraints like the timing argument, the statement that the MW and M31 must have been on the Hubble flow at very early times but still end up with their presently observed separation and relative velocity (Kahn & Woltjer 1959).…”
Section: Introductionsupporting
confidence: 57%
“…For example, Ref. [43] estimates for the local groups g ex ≈ 2.2 × 10 −2 a 0 . If all else was exact, with no measurement errors, and no departure from any of our assumptions, except that of isolation, then departures of σ M /σ from unity would only be due to the EFE, and be given, for g ex g, by 6 MOND predicts an acceleration discrepancy ≈ a0/ḡ, withḡ the larger of the internal and external accelerations.…”
Section: External-field Effect?mentioning
confidence: 99%
“…Fossils left over from this merging history orbit the galaxy as satellite galaxies, but the observed very significant phase-space correlation of satellite galaxies around the MW (Kroupa et al 2005;Pawlowski et al 2012;Pawlowski & Kroupa 2020), Andromeda (Metz et al 2007;Ibata et al 2013) and Cen A (Müller et al 2018) is inconsistent with the observed satellites being such fossils (Pawlowski 2018). The mutual alignment of the MW and Andromeda satellite population have not found an explanation in standard-dark-matter models, but appear to arise naturally in Milgromian dynamics (Bílek et al 2018;Banik et al 2018b). Moreover, given the non-detection of dark-matter-particles despite a significant effort to find them (Bertone & Tait 2018) and astronomical arguments suggesting dark matter not to exist (Kroupa et al 2010;Kroupa 2012, it is necessary to also begin to investigate if non-dark-matterbased models lead to objects which resemble observed galaxies.…”
Section: Introductionmentioning
confidence: 99%